2017
DOI: 10.1002/ejsp.2332
|View full text |Cite
|
Sign up to set email alerts
|

What do I gain from joining crowds? Does self‐expansion help to explain the relationship between identity fusion, group efficacy and collective action?

Abstract: Four studies were carried out to examine how identity fusion, self‐ and group efficacy, and collective action are related and what role self‐expansion plays in these relationships. In the pilot study, participants recalled their experience of participating in mass gatherings. The three other studies were conducted during mass gatherings organized for collective purposes: a music concert (Study 1), a bicycle activist event (Study 2), and Equality Days (Study 3). The results showed (a) a significant positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 52 publications
4
34
1
1
Order By: Relevance
“…These studies extend the concept of CE to prosocial behaviors in the organization context. Although previous studies have found associations between group efficacy and collective action (Besta et al, 2017) and between CE and undergraduate students' performance in teams (Brown, 2003), as far as we know, no study has explored or found associations between CE and prosocial behaviors in organizational contexts.…”
Section: Research Implicationsmentioning
confidence: 88%
“…These studies extend the concept of CE to prosocial behaviors in the organization context. Although previous studies have found associations between group efficacy and collective action (Besta et al, 2017) and between CE and undergraduate students' performance in teams (Brown, 2003), as far as we know, no study has explored or found associations between CE and prosocial behaviors in organizational contexts.…”
Section: Research Implicationsmentioning
confidence: 88%
“…And Talaifar et al (2020), found that students who were strongly fused with their university were more likely to remain in school up to a year later. Alternative studies indicate that one of the positive consequences of being fused with a group could be self‐expansion (Besta, Jaśkiewicz, Kosakowska‐Berezecka, Lawendowski, & Zawadzka, 2018), and that being fused with the romantic partner could lead to more constructive ways of coping with relationship conflicts and reduced vigilance for relationship threats (Walsh & Neff, 2018).…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
“…In contrast, strongly fused individuals reduce their willingness to fight and die for their group when they learn that other ingroup members would self‐sacrifice for it due to their moral principles and emotions toward the group as opposed to a pragmatic calculus about the costs and benefits associated to self‐sacrificial behavior (Paredes, Briñol, & Gómez, 2018). Regarding the mediators, a recent research has revealed two additional mechanisms, feelings of self‐expansion and group‐eficacy beliefs, that operate sequentially (Besta et al, 2018). These studies were conducted during various mass gatherings, including music festivals, a demonstration of bicycle activists and cycling lovers, and a protest of LGBT right supporters.…”
Section: Main Advances and Discoveries Since 2015 For Identity Fusionmentioning
confidence: 99%
“…By doing so, followers' own perceived efficacy and resources increase and they may gain or perceive that they gain access to some of their leader's rewards (see 16 ). Although this motivation has not been established in terms of fusion with an individual, recent research shows that self-expansion and, consequently, an increased sense of efficacy and agency, play important roles in the effects of identity fusion on collective action 19,20 . Hence, because fusing with other individuals can help people expand their self and thereby obtain new perspectives and capabilities (for instance, increased self-confidence, perceived competence and other traits as demonstrated by Besta, et al 19 ), fusion can indeed have a self-enhancing function.…”
Section: Introductionmentioning
confidence: 99%